Transmission specificities of plant viruses with the newly identified species of the Bemisia tabaci species complex. Issue 10 (3rd March 2014) - Polston, Jane E; De Barro, Paul; Boykin, Laura M
Abstract Bemisia tabaci has had a colorful nomenclatural past and is now recognized as a species complex. This new species framework has added many new areas of research including adding new insight into the virus transmission specificity of the species in the B. tabaci species complex. There is a wide disparity in what is known about the transmission of plant viruses by different members of the B. tabaci species complex. In this paper, we have synthesized the transmission specificities of the plant viruses transmitted by species belonging to the complex. There are five genera of plant viruses with members that are transmitted by species of the B. tabaci species complex. The transmission of viruses belonging to two of these, Begomovirus and Crinivirus, are well studied and much is known in regards to the relationship between species and transmission and etiology. This is in contrast to viruses of the genera, Torradovirus and Carlavirus, for which very little is known inregards to their transmission. This is the first attempt to integrate viral data within the new B. tabaci species complex framework. It is clear that matching historical transmission data with the current species framework is difficult due to the lack of awareness of the underlying genetic diversity within B. tabaci. We encourage all researchers to determine which species of B. tabaci they are using to facilitate association of phenotypic traits with particular members of the complex. © 2014 Society of Chemical Industry